2014
DOI: 10.1111/imm.12358
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal peptide‐induced tolerance and linked suppression: consequences of complement deficiency

Abstract: A role for complement, particularly the classical pathway, in the regulation of immune responses is well documented. Deficiencies in C1q or C4 predispose to autoimmunity, while deficiency in C3 affects the suppression of contact sensitization and generation of oral tolerance. Complement components including C3 have been shown to be required for both B-cell and T-cell priming. The mechanisms whereby complement can mediate these diverse regulatory effects are poorly understood. Our previous work, using the mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
(115 reference statements)
0
6
0
Order By: Relevance
“…The doses and concentration of the antigen are often directly correlated with the generation of active and cell-dependent regulatory mechanisms (Turley and Miller, 2010) or with the induction of anergy (Bitar and Whitacre, 1988) or even deletion of antigen-specific T cells (Critchfield et al, 1994;Liblau et al, 1996;Apostolou and von Boehmer, 2004;Judkowski et al, 2004). Likewise, immunological tolerance achieved by oral (Higgins and Weiner, 1988;Weiner, 2000;Weiner et al, 2011) and intranasal (Anderton et al, 1998;Fossati-Jimack et al, 2015) delivery of autoantigens has shown to be mediated by active suppressor mechanisms such as anti-inflammatory cytokines and regulatory cells (Chen et al, 1995;Weiner et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The doses and concentration of the antigen are often directly correlated with the generation of active and cell-dependent regulatory mechanisms (Turley and Miller, 2010) or with the induction of anergy (Bitar and Whitacre, 1988) or even deletion of antigen-specific T cells (Critchfield et al, 1994;Liblau et al, 1996;Apostolou and von Boehmer, 2004;Judkowski et al, 2004). Likewise, immunological tolerance achieved by oral (Higgins and Weiner, 1988;Weiner, 2000;Weiner et al, 2011) and intranasal (Anderton et al, 1998;Fossati-Jimack et al, 2015) delivery of autoantigens has shown to be mediated by active suppressor mechanisms such as anti-inflammatory cytokines and regulatory cells (Chen et al, 1995;Weiner et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the report that C3 is required for the rejection of fully MHC mis-matched kidney grafts (Pratt et al, 2002), we have shown, using the minor histocompatibility (HY) model of skin graft rejection, that C1q and C3, are required for the induction of tolerance rather than for rejection (Baruah et al, 2010), a finding that was subsequently confirmed by others (Bartel et al, 2013). Using C1q-, C3-, C4-and C5-deficient female mice we have also demonstrated that the classical pathway components including C3 are required for tolerance induction, whilst C5 plays no role (Fossati-Jimack et al, 2015). Of note, the C3-deficient mice used in our study cannot generate any intracellular C3a fragment as they lack the corresponding genetic region (Wessels et al, 1995).…”
Section: C1q Acting Independently Of Complement Activationmentioning
confidence: 68%
“…We also found no evidence of a defect in the ability of C3-deficient T cells to generate Treg using established in vitro protocols, arguing against an intrinsic T cell defect. We did, however, identify a role for C3 in the induction of the amino acid metabolising enzyme, nitric oxide-synthase-2 (Nos-2) (Fossati-Jimack et al, 2015), which has been shown to be crucial for Treg generation in a model of infectious tolerance (Cobbold et al, 2009). Thus, in the absence of C3, the induction of amino acid-depleting enzymes in DCs is impaired causing a reduced Treg generation possibly as a result of impaired downregulation of the mTOR pathway.…”
Section: C1q Acting Independently Of Complement Activationmentioning
confidence: 84%
“…Transplant rejection is associated with C3 deposition and related to complement activation ( 174 ). Counterintuitively, C1q as well as C3 appear to be protective with respect to allograft rejection as demonstrated by an earlier rejection of a solid organ transplant in C1qKO as well as C3KO mice ( 89 91 ). Intranasal tolerance induction failed in complement (C1q and C3) deficient mice ( 90 ).…”
Section: Resultsmentioning
confidence: 99%